STRUCTURAL AND FUNCTIONAL RESPONSES OF FISH ASSEMBLAGES TO DIFFERENT DRIVERS OF CHANGE - Turco, Gabriele
Biotic and abiotic factors synergistically act on natural systems. As a result ecological communities adjust their structural and functional responses to persist in a given area. Worldwide, marine ecosystems have been changing through time with increasing anthropogenic pressure in the last centuries leading to only 13.2% of the total marine environments in a ‘pristine’ state. The consequences of direct and indirect anthropogenic pressures may have on marine organisms can largely differ, with both negative and positive effects of drivers of change of human origin. In the span of three years for my PhD thesis, I performed different experiments with the main goal of examining how direct or indirect drivers of change may affect fish assemblages. For this purpose, I focussed on positive effects of protection activities within Marine Protected Areas (MPAs) in the Mediterranean Sea and potentially detrimental impacts of increasing CO2 concentrations in Italy, Japan, and Papua New Guinea. The first part of this thesis examined ecological responses within 11 Mediterranean Marine Protected Areas (MPAs) belonging to six different countries (France, Spain, Greece, Italy, Croatia, and Slovenia). I assessed whether and how MPAs can be successful in reaching their conservation goals (higher fish diversity and biomass than outside) and in re-establishing their trophic state (higher levels of top-down control inside their boundaries), despite differing management and protection schemes. Overall, results highlighted higher biomass levels both for whole fish assemblages and for commercial species targeted by small-scale and industrial fishery inside the 11 pilot MPAs. Overall predation rates were unaffected despite a few MPAs showing higher rates inside than outside their boundaries. The second part of this thesis tackled the direct and indirect effects of ocean acidification at an ecosystem level. Ecological surveys on both benthic habitat and fish assemblages were carried out in three different volcanic seeps belonging to ...